2017
DOI: 10.1523/jneurosci.0179-17.2017
|View full text |Cite
|
Sign up to set email alerts
|

Wild-Type Monomeric α-Synuclein Can Impair Vesicle Endocytosis and Synaptic Fidelity via Tubulin Polymerization at the Calyx of Held

Abstract: α-Synuclein is a presynaptic protein the function of which has yet to be identified, but its neuronal content increases in patients of synucleinopathies including Parkinson's disease. Chronic overexpression of α-synuclein reportedly expresses various phenotypes of synaptic dysfunction, but the primary target of its toxicity has not been determined. To investigate this, we acutely loaded human recombinant α-synuclein or its pathological mutants in their monomeric forms into the calyces of Held presynaptic termi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
74
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 65 publications
(80 citation statements)
references
References 65 publications
6
74
0
Order By: Relevance
“…A similar observation was made in mammalian Calyx of Held synapse, where acute elevation of monomeric and mutant a-synuclein levels decreased SV endocytosis with a frequency-dependent effect on SV exocytosis. This was also seen upon transgenic expression of a-synuclein (Xu et al 2016;Eguchi et al 2017). Overexpression of mutant a-synuclein also affects dopamine transporter trafficking on the pre-synaptic membrane, leading to dopamine dyshomeostasis (Kisos et al 2014).…”
Section: Pink1 and Parkin: Role In Mitophagy And Beyondmentioning
confidence: 91%
“…A similar observation was made in mammalian Calyx of Held synapse, where acute elevation of monomeric and mutant a-synuclein levels decreased SV endocytosis with a frequency-dependent effect on SV exocytosis. This was also seen upon transgenic expression of a-synuclein (Xu et al 2016;Eguchi et al 2017). Overexpression of mutant a-synuclein also affects dopamine transporter trafficking on the pre-synaptic membrane, leading to dopamine dyshomeostasis (Kisos et al 2014).…”
Section: Pink1 and Parkin: Role In Mitophagy And Beyondmentioning
confidence: 91%
“…The acute addition of α‐synuclein is a strength of these studies since it suggests a direct effect on these cellular processes. In one study, mutations were found to disrupt the effect on endocytosis (Eguchi et al ), providing an important negative control. We note however that the direct injection of recombinant protein also raises the possibility of toxicity that may not occur with expression by the cell.…”
Section: Over‐expression Of α‐Synucleinmentioning
confidence: 99%
“…The acute addition of asynuclein is a strength of these studies since it suggests a direct effect on these cellular processes. In one study, mutations were found to disrupt the effect on endocytosis (Eguchi et al 2017), providing an important negative syn syn Fig. 1 The Role of Synuclein in Exocytosis.…”
Section: Over-expression Of A-synucleinmentioning
confidence: 99%
“…The requirement for correctly functional microtubule dynamics during mitosis has driven extensive work on targeted and selective microtubule‐binding agents as “antimitotic” cancer chemotherapeutics, including paclitaxel, epothilone and vinca alkaloids . In research, the sheer breadth and spatiotemporal complexity of microtubule‐dependent biological roles presents an excellent opportunity for photopharmacological intervention, and microtubule‐targeting photopharmaceuticals such as PST‐1 have quickly moved on from chemical proof‐of‐concept to find diverse cellular and animal research applications . Due to the massive clinical utility of microtubule‐binding agents in cancer therapy, as well as the systemic side‐effects of conventional antimitotics, it is also of extensive interest to find more potent photoswitchable microtubule inhibitors and evaluate whether they can be guided by localised tumour illumination to act as tumour‐specific antimitotics that spare healthy tissues from chemotherapeutic damage.…”
Section: Introductionmentioning
confidence: 99%